2002
DOI: 10.1002/cncr.10281
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis in patients with craniopharyngiomas

Abstract: The functional single‐coordinate phosphine oxide ligands (4‐diphenylaminophenyl)diphenylphosphine oxide (TAPO), (4‐naphthalen‐1‐yl‐phenylaminophenyl)diphenylphosphine oxide (NaDAPO), and 9‐[4‐(diphenylphosphinoyl)phenyl]‐9H‐carbazole (CPPO), as the direct combinations of hole‐transporting moieties, and electron‐transporting triphenylphosphine oxide (TPPO) were designed and synthesized (amines or carbazole), together with their EuIII complexes [Eu(tapo)2(tta)3] (1), [Eu(nadapo)2(tta)3] (2), and [Eu(cppo)2(tta)3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 66 publications
3
44
0
2
Order By: Relevance
“…2,13,51,[55][56][57] One functional study using a corneal angiogenesis assay revealed that recurrent ACP samples had a significantly higher angiogenic potential than nonrecurrent ACP, but less than glioblastoma multiforme or arteriovenous malformations. 51 Imatinib-loaded microspheres reduced neovascularization in this model, but the use of this or other antiangiogenic approaches in patients has not been reported in the literature.…”
Section: Molecular Biology Of Tumor-associated Angiogenesismentioning
confidence: 99%
“…2,13,51,[55][56][57] One functional study using a corneal angiogenesis assay revealed that recurrent ACP samples had a significantly higher angiogenic potential than nonrecurrent ACP, but less than glioblastoma multiforme or arteriovenous malformations. 51 Imatinib-loaded microspheres reduced neovascularization in this model, but the use of this or other antiangiogenic approaches in patients has not been reported in the literature.…”
Section: Molecular Biology Of Tumor-associated Angiogenesismentioning
confidence: 99%
“…Compared with primary tumors, recurrent tumors display increased expression of growth factors and their receptors that normally regulate cellular proliferation, including platelet-derived growth factor receptor-a (PDGFR-a) and fibroblast growth factor-2 (FGF-2). 82,90,94 Upregulation of angiogenesis is another requirement for recurrence, as suggested by the increase in vascular endothelial growth factor (VEGF) expression in recurrent tumors. 98 b-catenin is a regulator of VEGF in other cancers 27 and likely mediates the angiogenic potential of craniopharyngioma cells via this mechanism.…”
Section: Tumor Recurrencementioning
confidence: 99%
“…Therefore, preventing the tumor cells from adapting to the hypoxic conditions may be an effective way to obviate the relapse of craniopharyngioma. Various studies have shown that the formation of new blood vessels, the angiogenesis, plays a significant role in tumor progression [24]. Possibly the cellular adaptation to hypoxia is a key factor of angiogenesis under hypoxic microenvironment within craniopharyngioma [19,23,24].…”
Section: Discussionmentioning
confidence: 99%